Counselling issues in familial hypertrophic cardiomyopathy. Issue 3 (March 1998) - Yu, B; French, J A; Jeremy, R W; French, P; McTaggart, D R; Nicholson, M R; Semsarian, C; Richmond, D R; Trent, R J
Abstract : To illustrate the variable clinical presentations and rates of progression in familial hypertrophic cardiomyopathy (FHC), phenotypes and genotypes were compared in three FHC families with different genetic defects. In the first family, the FHC abnormality was a protein truncating mutation (Gln969X) in the cardiac myosin binding protein C gene. The second family had a missense change (Asn755Lys) in the same gene. A missense mutation (Arg453Cys) in the cardiac beta myosin heavy chain gene was present in the third family. Penetrance associated with the Gln969X defect was 27% in the age range 0 to 40 years. This was considerably less than the 93% penetrance (0 to 40 years) observed in the two families with missense mutations. The variable penetrance in FHC, as well as the unpredictability of sudden cardiac death, complicates clinical diagnosis and management, including genetic counselling. Although a genetic disease with a predominantly adult onset, there are counselling issues in FHC which set it aside from other adult onset disorders.